2018
DOI: 10.4103/sja.sja_653_17
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided bilateral superficial cervical plexus block for thyroid surgery: The effect of dexmedetomidine addition to bupivacaine-epinephrine

Abstract: Background:The thyroid gland surgery is a common and painful procedure demanding analgesia. Many regional techniques are applied for anterior neck surgeries mostly assigned in relation to the involved cervical fascia. Dexmedetomidine (Precedex) is a selective alpha 2 adrenoceptor agonist which prolongs the sensory blockade duration of local anesthetics. Our study hypothesis is that ultrasound (US)-guided bilateral superficial cervical plexus block (BSCPB) may provide longer analgesia when adding dexmedetomidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In agreement with the current study, Elmaddawy et al [ 24 ] and Kannan et al [ 25 ] found that the time to first request for pethidine in ultrasound-guided superficial cervical plexus block receiving plain bupivacaine was approximately 7 h postoperative in patients undergoing thyroid surgery. However, Kendall et al [ 26 ] in their meta-analysis reported that patients undergoing orthopedic or spine surgeries experienced pain relief for up to 12 h postoperative when comparing erector spinae block with a control group.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the current study, Elmaddawy et al [ 24 ] and Kannan et al [ 25 ] found that the time to first request for pethidine in ultrasound-guided superficial cervical plexus block receiving plain bupivacaine was approximately 7 h postoperative in patients undergoing thyroid surgery. However, Kendall et al [ 26 ] in their meta-analysis reported that patients undergoing orthopedic or spine surgeries experienced pain relief for up to 12 h postoperative when comparing erector spinae block with a control group.…”
Section: Discussionsupporting
confidence: 92%
“…The patient remained sedated and could be awakened at any time during the operation, but the mean arterial pressure and heart rate decreased after the procedure, requiring the anesthesiologist to pay close attention to hemodynamic changes during the operation. Elmaddawy et al 96 mixed bupivacaine, epinephrine, and dexmedetomidine in thyroid surgery for bilateral CPB. The results demonstrated that applying 1 µg/kg dexmedetomidine around the cervical plexus prolonged the analgesic time during and after surgery, reduced the demand for opioids, and reduced the heart rate.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“…The involvement of the noradrenergic system in the perception of pain is known since studies show that noradrenergic neurons in the locus ceruleus mediate analgesia via axon terminals in the spinal dorsal cord , besides several agonist drugs of the alpha noradrenergic receptor show analgesic effect, such as dexmedetomidine and clonidine . No influence of yohimbine on the effect of the compounds was observed, evidencing the absence of noradrenergic participation in the activity of the compounds.…”
Section: Discussionmentioning
confidence: 63%